Examination of the Effect of Sensor Properties on the Secondary Battery Model in Simulation Environment - Lakatos, I.; Kőrös, P.; Hajdu, F. (Acta Technica Jaurinensis, 2014)
The aim of the presented method is to develop a simulation environment which is able to handle diagnostic tools of electric vehicles. Steps of forming the simulation environment are described in the article. Implementation of real sensors is not dealt with. The structure of a modular and easily adaptable testing approach is explained.